A Study on Porous Sealing Efficacy of hydrophilic Admixture on Blended Cement Concrete - Krishnaraj, L; T. Ravichandran, P; V.A.Karthik, M; Satheeshram Avudaiyappan, N; ., . (International Journal of Engineering and Technology, 2018)
The life of the concrete is strongly influenced by durability parameters. The permeability is one of the main characteristics influencing the durability of concrete. The concrete is more permeable due to the ingress of water, oxygen, chloride, sulphate, and other potential deleterious substances. The durability of concrete is mainly affected by pore structure system of concrete and addingthe supplementary cementitious materials (SCM), such as fly ash, slag cement, and silica fume can be decrease permeability. Crystalline technology enhances the strength of concrete by filling the poresand micro-cracks with non-dissolvable substances. To study the efficiency of crystalline formation in concrete in terms of more permeable should be guaranteed through a specific technique.The effectiveness of crystalline waterproofing system with partial replacement cement by GGBS is studiedin terms of strength and durability. The performance of the two different types of crystalline waterproofing integral admixtures has been studied for compressive strength, Split tensile strength, workability, water permeability, Rapid chloride permeability test and porosity in this paper.The early strength increased in GGBS with crystalline admixture concretes compare to the control concrete. No significant strength reduction is observed in GGBS concretes with crystalline admixture when replaced with 20% and 40% of cement than control concrete.Â Â